Travel-Associated Rabies in Pets and Residual Rabies Risk, Western Europe - Ribadeau-Dumas, Florence (Emerg Infect Dis, 2016)
In 2015, countries in western Europe were declared free of rabies in nonflying mammals. Surveillance data for 2001–2013 indicate that risk for residual rabies is not 0 because of pet importation from countries with enzootic rabies. However, the risk is so low (7.52 × 10(−10)) that it probably can be considered negligible.